Digital transformation of islamic boarding school-based MSMEs in improving local economic competitiveness: A systematic literature review (SLR) - Achmad Luthfi Chamidi Chamidi; Samsul Huda; Agus Eko Sujianto; Rokhmat Subagiyo; Binti Nur Asiyah (Universitas Negeri Surabaya, 2025)
This study systematically analyzes the digital transformation of Islamic boarding school-based Micro, Small, and Medium Enterprises (MSMEs) and their role in enhancing local economic competitiveness, with a focus on digital marketing and promotion strategies. Using a Systematic Literature Review (SLR) method, this study synthesizes findings from 14 relevant articles published between 2014 and 2025. The results show that Islamic boarding school MSMEs actively adopt digital marketing through various platforms such as social media (Facebook, Instagram, Instagram Reels, Twitter) and e-commerce to expand market reach and significantly increase sales. Islamic boarding schools are identified as a vital supporting ecosystem, providing human resources (students), alumni networks, and a unique foundation of sharia values, all of which support MSMEs economic activities. However, challenges such as lack of digital literacy, limited capital, and online market competition remain. Therefore, multi-sector collaboration (e.g., the One Pesantren One Product/OPOP program) and institutional and community involvement are key to the success of digital-based MSMEs empowerment. A conceptual visualization model presented in this study illustrates the synergistic relationship between the role of Islamic boarding schools, the development of MSMEs digital capacity, the adoption of marketing strategies, and increasing local economic competitiveness.